The Influence of Social Media Influencer’s Trustworthiness on Engagement, Expected Value and Purchase Intention - Puteri Lefina, Ziyan; Hidayat, Anas (Green Publisher Indonesia, 2022)
In this digital age, it is indisputable that the internet has become an essential part of human existence and has had a great impact on society. By having this condition, businesses may consider allocating budgets to use influencer marketing as a marketing strategy. This study aimed to examine whether followers' perception of a social media influencer's trustworthiness can lead to responses to the influencers' recommended brands, specifically brand engagement in self-concept, expected brand value, and intention to purchase recommended brands. This study used non-probability sampling with the criteria of Indonesians who follow an influencer. The data was gathered by distributing an online questionnaires via Google Form to a total of 264 respondents. The data analysis technique utilized is SEM, which was conducted using the AMOS 22 application. The results showed that perceived influencer trustworthiness positively influence brand engagement in self-concept, brand expected value and intention to purchase recommended brand. While, brand engagement in self-concept positively influence brand expected value and intention to purchase recommended brand. Also, brand expected value positively influence intention to purchase recommended brand. This research will assist in understanding how social media influencers' recommendations influence customers' perceptions and behavior patterns.